Eksistensi Sultan Ground dalam Hukum Tanah Nasional di Desa Srigadung Kecamatan Sanden Kabupaten Bantul Prrovinsi Daerah Istimewa Yogyakarta - Jose Marcus Fernando (Magister Administrasi Publik, 2010)
The paper examines the perception of the exixtence of Sultan Ground in Srigading village, Bantul, Yogyakarta Special Region (DIY) province. This study show that existence of Sultan Ground in the village is fully recognized and acknowledged by the local community. They acknowledge that the land in their villages is not private land or government land (country), but belongs to the Sultan. Local people control the land with the status of land use right, which means that they can use the Sultan Ground for various purposes, such as agriculture/ livestock, economic activity, tourism, and settlements. Public recognitions of the Sultan Ground’s is in line with the rule of law. In that regards, DIY Province has special land arrangements, which are different from those in the land law that applies nationally.